2017
DOI: 10.1186/s12866-016-0923-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel bovine enterovirus possessing highly divergent amino acid sequences in capsid protein

Abstract: BackgroundBovine enterovirus (BEV) belongs to the species Enterovirus E or F, genus Enterovirus and family Picornaviridae. Although numerous studies have identified BEVs in the feces of cattle with diarrhea, the pathogenicity of BEVs remains unclear. Previously, we reported the detection of novel kobu-like virus in calf feces, by metagenomics analysis. In the present study, we identified a novel BEV in diarrheal feces collected for that survey. Complete genome sequences were determined by deep sequencing in fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
(50 reference statements)
0
17
0
Order By: Relevance
“…The indels may not be strictly neutral, but if they are associated with some fitness cost, the detrimental phenotypic changes are likely to be suppressed by some secondsite mutations (see below). In some cases, such indels appeared to even be advantageous, judging by their strong conservation in representatives of a given picornavirus species, as is the case, for example, with the triplication of the VPg gene in the FMDV RNA (276,277) and the duplication of the 5=-terminal cis-element of the bovine enterovirus RNA (278,279). Conserved duplications in untranslated and coding RNA regions of other viruses have been described as well (cf.…”
Section: (Relative) Neutrality Of Various Mutationsmentioning
confidence: 96%
“…The indels may not be strictly neutral, but if they are associated with some fitness cost, the detrimental phenotypic changes are likely to be suppressed by some secondsite mutations (see below). In some cases, such indels appeared to even be advantageous, judging by their strong conservation in representatives of a given picornavirus species, as is the case, for example, with the triplication of the VPg gene in the FMDV RNA (276,277) and the duplication of the 5=-terminal cis-element of the bovine enterovirus RNA (278,279). Conserved duplications in untranslated and coding RNA regions of other viruses have been described as well (cf.…”
Section: (Relative) Neutrality Of Various Mutationsmentioning
confidence: 96%
“…In addition to type 1 recombinant EV-G, second type of recombinant EV-G (we call type 2 recombinant EV-G in this study), which carried the PLCP gene in place of viral structural genes, has been identified in a Chinese pig farm (Wang et al, 2018). The PLCP gene is encoded in the ORF1 of the genome of torovirus, a member of family Coronaviridae, and the order Nidovirales (Conceição-Neto et al, 2017;Knutson et al, 2017;Shang et al, 2017;Tsuchiaka et al, 2017;Wang et al, 2018). The PLCP of nidoviruses serves as a protease to cleave viral gene 1 polyproteins to mature proteins (Mielech et al, 2014).…”
Section: Figmentioning
confidence: 99%
“…By using a metagenomics approach, we have detected the genomes of EV-G1, 2, 3, 4, 6, 9, 10 and a new type of EV-Gs in feces of pigs with or without diarrhea in Japan (Tsuchiaka et al, 2017). Among them, 16 sequences of EV-G1 and one isolate of EV-G2 show an insertion of a papain-like cysteine protease (PLCP) gene from porcine torovirus at the 2C-3A junction sites (Tsuchiaka et al, 2017) (Fig. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…VP1 represents a highly variable region in the enteroviral genome; VP1 sequence variations are useful for determining the genotypes of species by use of molecular methods (8,9). On the basis of the sequence analysis of capsid proteins, 5, 7, and 20 genotypes of EV-E (EV-E1 to EV-E5), EV-F (EV-F1 to EV-F7), and EV-G (EV-G1 to EV-G20), respectively, have been identified (1, [10][11][12][13].…”
mentioning
confidence: 99%